Evaluation on steel corrosion in water-based drilling fluids: Inhibitors and scale involvement - Yahya, S. (Elsevier B.V., 2022)
The purpose of this research is to investigate the behaviour of steel corrosion protection in four different fluids; seawater, tap water, 10 ppg sodium chloride (NaCl) and 12 ppg potassium formate (HCOOK) which are typically used as drilling fluid in oil and gas platform. Corrosion assessment of steel exposed to simulated underbalanced drilling (UBD) wells has been examined via immersion test by weight loss technique. The experiment was carried out in high pressure-high temperature (HPHT) for 30 h in the laboratory stirred autoclave. Two commercial corrosion inhibitors were used in studying the behaviour of the surface protection. Results showed the corrosion rate was dependent on the types of fluids and inhibitors used. The order of corrosion severity or rate of steel corrosion in the individual fluids are; tap water < HCOOK < seawater < NaCl. The observation on the surface morphology through electron microscope depicted the uniform corrosion was the predominantly attack rather pitting and oxide scale formation. The scale formation on the steel surface were discussed. Â© 2022 Elsevier B.V.